Análise do comportamento da fluidodinâmica do leito de jorro com misturas de tamanho de partículas - Bacelos, Marcelo Silveira (2006)
This research study presents an investigation to quantify the stability of spouting regimes (by pressure fluctuations) and particle segregation level in conical spouted beds operated with a variety of particle combinations with uniform size or size distribution. In the presence of glycerol, a study on the effect of interparticle forces in the conical spouted bed fluid dynamics behavior with inert particle mixtures was also employed. Data show that, at a standard deviation from pressure signals of 50 Pa, in beds composed of inert particle of uniform size or size distribution stable spouting regime can be achieved. Moreover, the analysis of segregation indexes revealed that particle segregation becomes less pronounced as dpL/dpS is reduced from 2.85 to 1.98 and bed height is increased from 0.105 to 0.195 m. When glycerol is added into the bed, the results show that the dimensionless minimum spouting velocity (vmj/vmj0) does not change significantly with increase in glycerol concentration for the reference mixture. However, for all other mixtures of dpL/dpS > 1.98 employed, vmj/vmj0 increases with increase in the glycerol concentration into the bed, and this increase is more pronounced for flat and binary mixtures. The dimensionless of minimum spouting pressure drop (∆Pmj/∆Pmj0) decreases with increase in the glycerol concentration for all mixtures used. The application of a theoretical analysis, predicting the interparticle forces, shows that the change in minimum spouting condition as glycerol concentration increases can be explained by the magnitude of these forces.